Correlation between complement component levels and disease severity in dengue patients in Indonesia - Yamanaka, Atsushi; Hendrianto, Eryk; Mulyatno, Kris C; Susilowati, Helen; Ginting, Amor P; Sary, Dian D; Soegijanto, Soegeng; Konishi, Eiji (Japanese journal of infectious diseases, 2013)
Dengue hemorrhagic fever (DHF) is a severe form of dengue fever (DF). Recent in vitro studies indicate that complement reduces the infection-enhancing activity of dengue antibodies, suggesting its in vivo role in controlling viremia levels and disease severity. In this study, the complement hemolytic activity (CH50) and levels of complement components and related factors in dengue patients in Indonesia were assessed. Based on the number of days since fever onset, DF patients were compared with patients at the DHF pre-critical phase who showed deterioration within 2 days. The mean CH50 values and levels of C2, C4, and factors B and H in the DHF pre-critical phase group were significantly lower than those in the DF group. The mean CH50 values were significantly correlated with C4, factor B, or factor H levels, indicating their responsibility for reduced CH50 values. Furthermore, a significantly higher proportion of the DHF pre-critical phase group (78%) than the DF group (33%) was positive for the nonstructural protein 1 (NS1) antigen. These results suggested that antibody-dependent enhancement of infection occurs during a period of low complement activity, which is associated with NS1 levels during the acute phase in some patients, thereby leading to increased viremia levels and greater disease severity.